DINAMIKA PELAKSANAAN ELECTRONIC GOVERNANCE PEMERINTAHAN DAERAH DI INDONESIA - Aswin Aswin; Meti Mediyastuti Sofyan (Kebijakan : Jurnal Ilmu Administrasi, 2022)
Developments in the realm of information technology continue to change every year. The existence of the internet makes it easier for everyone to find something through their electronic devices, especially cellphones or computers as a medium. Internet users in Indonesia in the latest report, the number of internet users in Indonesia reached 202 million or 73.7% of the total population of 274.9 million in January 2021. Almost all of the Indonesian population uses internet facilities, this has become an infrastructure for the community to reach the internet network. This condition is an opportunity for new media in a public service process carried out by the Indonesian government. The existence of the internet and mobile computing in public service activities which are identical to the use of paper has now become a new era, namely paperless being one of the efficiency of public service activities. Existing resources in e-government activities are not only related to facilities and infrastructure, but also human resources of state civil servants need to have the ability to operate an e-government system that has been designed in such a way. The progress of implementing e-government in Indonesia is faced with several challenges and still has shortcomings. These challenges and shortcomings include an equitable internet network infrastructure, human resources to operate features and services, and community culture related to digital literacy. There is still a need for improvement in the implementation of e-government in Indonesia in order to achieve excellent public services for the community.